THE EFFECT OF MOZART MUSIC IN REDUCING ANXIETY OF ENGLISH SPEAKING IN PUBLIC (EXPOSURE JOURNAL, 2013)
The study used an experimental method namely a quasy-experimental design. The population of the study was consist of 260 subject from ten classes. The sampel one was purpossive sampling. The researcher collected data by using four instrument, they are questionnaire, observation, and scale of behavior. The result showed that Mozart gave effect in reducing subjectsâ anxiety of English speaking in public. It was proved by the total subjects is 8 students for very high anxiety and 7 students for very low anxiety before given treatmen; while after given treatmen, there are only 4 subjects for very high anxiety and 10 subjects for very low anxiety (look at the table 7 and 9). In other hand, the data support by Paired Sample Correlation table showed that score between pretest and posttest by 32 responden = 0,874; the significance or p was 0,000. The norm said that if the significance showed under 0, 05 (p < 0, 05), it means that H1 is accepted and H0 is refused. So, conclusion for the research is Mozart Effect can reduce the studentsâ anxiety of English speaking in public. The findings of the research were significant because p < 0, 05.Keywords: Effect, Mozart, Music, Anxiety, SpeakingPenelitian ini menggunakan metode eksperimen yaitu desain kuasi-eksperimental. Populasi dari penelitian ini adalah terdiri dari 260 subjek dari sepuluh kelas. Sampelnya adalah purposive sampling. Peneliti mengumpulkan data dengan menggunakan empat instrumen, antara lain; kuesioner, observasi, dan skala perilaku. Hasil penelitian menunjukkan bahwa Mozart memberi efek dalam mengurangi kecemasan dari subjek berbicara bahasa Inggris di depan umum. Hal itu dibuktikan dengan total subyek adalah 8 siswa untuk kecemasan yang sangat tinggi dan 7 siswa untuk kecemasan yang sangat rendah sebelum perlakuan diberikan; sementara setelah diberikan perlakuan, hanya ada 4 mata pelajaran untuk kecemasan yang sangat tinggi dan 10 mata pelajaran untuk kecemasan yang sangat rendah. Di sisi lain, dukungan data dengan Paired Sample tabel korelasi menunjukkan bahwa skor antara pretest dan posttest oleh 32 responden = 0874; signifikansi p adalah 0,000. Norma mengatakan bahwa jika signifikansi menunjukkan di bawah 0, 05 (p <0, 05), itu berarti bahwa H1 diterima dan H0 ditolak. Jadi, kesimpulan untuk penelitian ini adalah Efek Mozart dapat mengurangi kecemasan siswa berbahasa Inggris di depan umum. Temuan penelitian ini adalah penting karena p <0, 05.Kata Kunci: Pengaruh, Mozart, Musik, Kecemasan, Berbicara